Evaluating Stress-Mediated Microbial Pathogenesis in Golden Shiners, Notemigonus crysoleucas - Kaimal, Sindhu; Farmer, Bradley D.; Renukdas, Nilima N.; Abdelrahman, Hisham A.; Kelly, Anita M. (Frontiers in Physiology, 2022)
Flavobacterium covae (columnaris) is a microbial pathogen of the Golden Shiner (Notemigonus crysoleucas), a principal bait species. We investigated the effects of density and water temperature on the survival of fish subjected to a columnaris challenge and whether flow cytometry (FCM) could be a fast and reliable method to distinguish and enumerate F. covae populations from water and fish in experimental tanks. Juvenile Golden Shiners averaging 2.62 (±0.78 S.D.) g (negative for F. covae) were used in simultaneous trials at 22ºC and 28ºC in two ultra-low flow-through systems: each consisting of four treatments and five replicates per treatment. Treatments were fish stocked at either 600 fish/m3 or 2,400 fish/m3 and either challenged with F. covae or not; survival was observed for 48 hr after challenge. Samples of water and fish tissue were obtained for FCM enumerations and validation by qPCR. No significant differences in survival were recorded between density treatments; however, high temperature and columnaris challenge treatments showed significantly higher mortality. Bacterial enumeration (number/mL) by FCM highly correlated with bacterial counts r=0.81 (P=0.001) in the water samples. Higher water temperatures may have increased columnaris infections and mortality in Golden Shiners. Flow cytometry is a reliable method of enumerating F. covae from experimental tank water samples.